1988
DOI: 10.1063/1.453903
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of metal cluster reaction kinetics on charge state. I. Reaction of neutral (Nbx) and ionic (Nb+x, Nb−x) niobium clusters with D2

Abstract: The effect of charge state on niobium cluster chemisorption kinetics is explored via measurement of the relative rates of D2 activation by Nb−x, Nbx, and Nb+x containing up to 28 atoms. The presence of the + or − charge is found to have only a minor effect on rate for the majority of the clusters, with the reactivity of the ions being generally within a factor of 2.5 of the corresponding neutrals. The excess charge does, however, have a profund influence on reaction rate for a number of clusters in the 7≤x≤16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(33 citation statements)
references
References 20 publications
2
31
0
Order By: Relevance
“…For both V + 12 and Nb +/0 12 , experiment and theory have found evidence for the presence of different isomers. 17,47,48 However, in case of Ta + 12 it is impossible to either proof or disproof the existence of isomeric structures in the molecular beam, as the vibrational spectrum shows only few and very weak peaks.…”
Section: Resultsmentioning
confidence: 99%
“…For both V + 12 and Nb +/0 12 , experiment and theory have found evidence for the presence of different isomers. 17,47,48 However, in case of Ta + 12 it is impossible to either proof or disproof the existence of isomeric structures in the molecular beam, as the vibrational spectrum shows only few and very weak peaks.…”
Section: Resultsmentioning
confidence: 99%
“…As one of the key factors to understand the catalytic mechanism, adsorption behaviors of gas molecules on metal clusters have been studied widely both experimentally and theoretically [2][3][4][5][6][7][8][9][10][11]. It has been found that the adsorption properties change significantly as a function of cluster size for many systems, such as H 2 , D 2 , and N 2 on Fe n [2,3] and Nb n clusters [4][5][6][7][8], CO on different metal clusters [9], and O 2 on Au clusters [10,11]. In many cases, the different chemisorption reactivities have correlations to the electronic structures of metal clusters, such as electron affinity (EA) or ionization potentials (IP).…”
Section: Introductionmentioning
confidence: 99%
“…The rates of the chemisorption of H 2 , D 2 , and N 2 on Fe n , and Nb n (n = number of atoms) clusters and those of CO on different metal clusters can vary by several orders of magnitudes as a function of n [1][2][3][4][5][6]. For W n , a sharp jump of the reactivity towards N 2 chemisorption is detected at liquid nitrogen temperature as well as room temperature as n exceeds 15 [7,8].…”
Section: Introductionmentioning
confidence: 93%